2012
DOI: 10.1111/j.1468-5973.2012.00663.x
|View full text |Cite
|
Sign up to set email alerts
|

Media Reporting of Nuclear Emergencies: The Effects of Transparent Communication in a Minor Nuclear Event

Abstract: IN 2008, a nuclear event occurred at Krško nuclear power plant in Slovenia. Even though it was classified as level 0 on International Nuclear Event Scale, the transparency policy of the Slovenian nuclear safety authorities prompted it to notify the international community. This was the first time that the European Community Urgent Radiological Information Exchange (ECURIE) notification system was used outside the exercise framework.The event was reported in all major European. In this contribution, we report o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 20 publications
1
20
0
1
Order By: Relevance
“…The results indicate that these articles focused most heavily on conflict, responsibility, and economic interest (Lazic, 2013). Lastly, Perko et al (2012) conducted a content analysis of over 200 articles published in spoken and printed media in Slovenia and other countries to examine the media coverage of a nuclear event in Slovenia. The primary research question was whether a nuclear event attracts high media attention, even in the circumstance of a minor event and a transparent communication policy.…”
Section: Media Coverage Of Nuclear Powermentioning
confidence: 98%
See 2 more Smart Citations
“…The results indicate that these articles focused most heavily on conflict, responsibility, and economic interest (Lazic, 2013). Lastly, Perko et al (2012) conducted a content analysis of over 200 articles published in spoken and printed media in Slovenia and other countries to examine the media coverage of a nuclear event in Slovenia. The primary research question was whether a nuclear event attracts high media attention, even in the circumstance of a minor event and a transparent communication policy.…”
Section: Media Coverage Of Nuclear Powermentioning
confidence: 98%
“…It is noteworthy that the subtheme 'safety' was most prevalent in 2011 in both newspapers, which may be attributed to the 2011 Fukushima nuclear disaster in Japan. Previous studies have demonstrated that even minor nuclear incidents result in significant media attention (Perko et al, 2012). Indeed, the nuclear incident in Japan drew media attention immediately and prompted wide coverage in Chinese newspapers (Thomson, 2011).…”
Section: Explanations Of the Findingsmentioning
confidence: 98%
See 1 more Smart Citation
“…The high media interest for the Fukushima accident does not come as a surprise. Previous research has demonstrated that even nuclear events which are rated as zero on the INES generate significant media attention (Perko et al 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Research on media reporting about nuclear emergencies proves that even without radiological consequences, those events are considered newsworthy. For instance, the event at Krško nuclear power plant in Slovenia (2008) was classified as level 0 on International Nuclear Event Scale, however, it was reported in all major European media (Perko et al, 2012a). Another aspect of media effect on communication to public is that journalists work under constant pressure of deadlines, competition with other reporters (Cottle and Ashton, 1999, Scott, 2005, Slovic, 1986) and expectations of little margin for errors.…”
Section: Introductionmentioning
confidence: 99%